ANALYSIS AND DESIGN OF ERP INFORMATION SYSTEMS USING WAREHOUSE MANAGEMENT MODULES AT PT XYZ - Priyanggodo, Dyas Yudi; Sugiyani, Yani; Yanuardi, Yanuardi; Destriana, Rachmat; Herdiansah, Arief (Universitas Muhammadiyah Tangerang, 2022)
Company PT. XYZ works in the electronics industry. Commodity storage in warehouses increases with output. Therefore, there is a problem at company are the absence of data integration between divisions so that data sharing does not occur in real time and causes the recording of the number of goods incorrect. As a result, there is a discrepancy between the number of items listed on the Stock Card and the number of items in the warehouse. Operations of the Warehouse Sub Division at PT. XYZ must be supported by an information system. The methodology used in this research is RAD. The author examines the company's operational business procedures. Based on this research, the authors built an ERP system with the Odoo application and designed the proposed business processes, focusing on the Warehouse Management module that best fits the needs of the organization. In addition, Users will test the designed system before implementing it in business. The results of this study are the Warehouse management module in the Oodo application which has been adapted to business conditions and needs and can help businesses more easily solve warehouse operational problems at PT. XYZ.